Aviation Dentistry: is it an Unexplored Field of Dentistry? A Cross-Sectional Study - Kajol Shetty; Sindhu R; Sunayana Manipal; Prabu D; Raj Mohan; Bharathwaj V V (Journal of Aerospace Technology and Management, 2020)
Background: There is an increase in the number of flight travellers and with it comes the risks of developing in-flight dental conditions that evokes pain at higher altitudes. The knowledge about such conditions are necessary among the dentists to prevent such phenomena. Aim: To assess the knowledge and familiarity about aviation dentistry among dentists. Methodology: A cross-sectional questionnaire-based study conducted among 170 postgraduates and dental professionals in a private dental institution. A pilot study was conducted among 30 individuals, and the questionnaire was validated. Data was analysed by SPSS package 20. Descriptive statistics and chi-square tests were used. Results: 61.8% of the individuals were not familiar with the term aviation dentistry. A statistically significant association was found between familiarity with aviation dentistry and the qualification of the dentists and also between familiarity with aviation dentistry and years of experience of the dentists with a p value < 0.05. Conclusion: The study result shows the lack of knowledge about aviation dentistry among postgraduates and dental professionals.